2016
DOI: 10.1299/jtst.2016jtst00018
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of improper backfilling in vertical borehole

Abstract: Vertical ground heat exchanger (GHE) is widely being used to exchange heat into the ground by using the system of ground source heat pump (GSHP). The stability and thermal performance of GHE mainly relate to the grout, the advantages of GHE can be negated if the grout is not backfilled properly. In order to study the influence of grout backfilling in a vertical GHE, this study established a 2D steady-state heat conduction model, which simulated 4 cases as follows: (1) fine backfilling, (2) porous backfilling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They found that debonding at the backfill/pipe interface has greater significance than debonding between grout and surrounding formation. Chen and Mao [28] studied the influence of grout backfilling, estimating the thermal resistance through a 2D steady-state heat conduction model in four different cases: (1) fine backfilling, (2) porous backfilling, (3) hole-wall delaminating, and (4) pipe-wall delaminating. The comparison of performance shows that the heat transfer rate per unit length at the borehole wall decreases by 6.3%, 41.5%, and 78.4%, respectively, in the case of porous backfilling, hole-wall delaminating, and pipe-wall delaminating, with pipe-wall detaching having the worst impact on the BHE performance.…”
Section: Introductionmentioning
confidence: 99%
“…They found that debonding at the backfill/pipe interface has greater significance than debonding between grout and surrounding formation. Chen and Mao [28] studied the influence of grout backfilling, estimating the thermal resistance through a 2D steady-state heat conduction model in four different cases: (1) fine backfilling, (2) porous backfilling, (3) hole-wall delaminating, and (4) pipe-wall delaminating. The comparison of performance shows that the heat transfer rate per unit length at the borehole wall decreases by 6.3%, 41.5%, and 78.4%, respectively, in the case of porous backfilling, hole-wall delaminating, and pipe-wall delaminating, with pipe-wall detaching having the worst impact on the BHE performance.…”
Section: Introductionmentioning
confidence: 99%